Chemical Aspects of the Primary Ionization Mechanisms in Matrix-Assisted Laser Desorption Ionization. Issue 6 (December 2014) - Molin, Laura; Crotti, Sara; Seraglia, Roberta; Czarnocki, Zbigniew; Szawkało, Joanna; Maurin, Jan K.; Pluciński, Franciszek A.; Traldi, Pietro
It has been proposed that the primary ionization mechanism occurring in matrix-assisted laser desorption ionization (MALDI) experiments originates from the presence, in the solid-state matrix-analytes sample, of matrix dimers. These species are formed by the interaction of carboxylic groups present in the matrix molecules with the formation of strong hydrogen bonds. Theoretical calculations proved that the laser irradiation of these structures leads to one or two H-bridge cleavages, giving rise to an "open" dimer structure or to disproportionation with the formation of MH + and [M – H] − species. The ions so formed can be considered highly effective in their reaction with analyte ions, leading to their protonation (or deprotonation). To achieve further evidence for these proposals, in the present study the energetics of the reactions of ions from different aromatic carboxylic acids with two amino acids (glycine and lysine) and three multipeptides (gly-gly, gly-gly-gly and gly-gly-gly-gly) was investigated. The lowest Δ G values were obtained for 2, 5-dihydroxybenzoic acid, widely employed as the MALDI matrix. Also, for p -nitrobenzoic acid the reaction is slightly exothermic, while for the other aromatic carboxylic acids derivatives positives values of Δ G are present.